Blueberry Supplementation in Neuronal Health and Protective Technologies for Efficient Delivery of Blueberry Anthocyanins - Tran, Phuong H.L. (Biomolecules, 2021)
Blueberries are consumed as healthy fruits that provide a variety of benefits to the nervous system. Scientists have found that blueberries can be used as a daily edible source for supplementation to prevent and minimize complexities of age-related diseases as well as to improve learning and memory in children. Anthocyanins are the most mentioned compounds among the components in blueberries, as they play a major role in providing the health benefits of this fruit. However, while they are highly active in impeding biological impairment in neuronal functions, they have poor bioavailability. This review focuses on neurological investigations of blueberries from in vitro cell studies to in vivo studies, including animal and human studies, with respect to their positive outcomes of neuroprotection and intervention in neurodegenerative conditions. Readers will also find information on the bioavailability of anthocyanins and the considerable factors affecting them so that they can make informed decisions regarding the daily consumption of blueberries. In this context, the ways in which blueberries or blueberry supplementation forms are consumed and which of these forms is best for maximizing the health benefits of blueberries should be considered important decision-making factors in the consumption of blueberries; all of these aspects are covered in this review. Finally, we discuss recent technologies that have been employed to improve the bioavailability of blueberry anthocyanins in the development of effective delivery vehicles supporting brain health.